2004
DOI: 10.1080/312703002764
|View full text |Cite
|
Sign up to set email alerts
|

ENDOTRACHEALINTUBATION ANDESOPHAGEALTRACHEALCOMBITUBEINSERTION BYREGULARAMBULANCEATTENDANTS: A COMPARATIVETRIAL

Abstract: There were similar rates of successful insertion/ventilation with the ETC and ETI. ETI insertion success was lower without mannequin practice. ETI skill erosion was partially mitigated by additional field experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…44 In several controlled clinical trials involving both inhospital and out-of-hospital resuscitation of adults, providers with all levels of experience were able to insert the esophageal-tracheal tube and deliver ventilation comparable to that achieved with endotracheal intubation. 35,[45][46][47][48] In a retrospective study no difference in outcome was observed in patients treated with the esophageal-tracheal tube compared with those treated with endotracheal intubation. 38 The esophageal-tracheal tube is reported to provide successful ventilation during CPR in 62% to 100% of patients.…”
Section: Esophageal-tracheal Tubementioning
confidence: 99%
See 1 more Smart Citation
“…44 In several controlled clinical trials involving both inhospital and out-of-hospital resuscitation of adults, providers with all levels of experience were able to insert the esophageal-tracheal tube and deliver ventilation comparable to that achieved with endotracheal intubation. 35,[45][46][47][48] In a retrospective study no difference in outcome was observed in patients treated with the esophageal-tracheal tube compared with those treated with endotracheal intubation. 38 The esophageal-tracheal tube is reported to provide successful ventilation during CPR in 62% to 100% of patients.…”
Section: Esophageal-tracheal Tubementioning
confidence: 99%
“…38 The esophageal-tracheal tube is reported to provide successful ventilation during CPR in 62% to 100% of patients. 35,[45][46][47][48][49] For healthcare professionals trained in its use, the esophagealtracheal tube is an acceptable alternative to both bag-mask ventilation (Class IIa, LOE C) or endotracheal intubation (Class IIa, LOE A) for airway management in cardiac arrest.…”
Section: Esophageal-tracheal Tubementioning
confidence: 99%
“…In addition, we include in the present review nine studies making comparison with non-simulation instruction [71][72][73][74][75][76][77][78][79] and eight studies making comparison with alternate simulation. 71,[80][81][82][83][84][85][86] These comparisons with active interventions were included in previous meta-analyses. 14,15 Three articles omitted the number of trainees; we contacted these authors and two provided needed information.…”
Section: Trial Flowmentioning
confidence: 99%
“…71,[80][81][82][83][84][85][86] For these studies, we conducted meta-analyses according to seven (2) 14 (28) Randomized 2-group (3) 27 (56) Sampling: No. institutions (maximum 1.5) 1 (0.5) 37 (74) 2 ( Subjective (1) 4 (8) Objective (3) 46 (92) Validity evidence (maximum 3) Content (1) 7 (14) Internal structure (1) 3 (6) Relations to other variables (1) 3 (6) Data analysis: appropriate (maximum 1)…”
Section: Quantitative Synthesis: Comparative Effectivenessmentioning
confidence: 99%
“…91 There is less robust support for the laryngeal mask airway, and although the Combitube has been demonstrated to be efficacious in the hands of skilled physicians as an alternative to tracheal intubation, there is evidence that it may be less so when used by minimally trained individuals. 92,93 An adjunct to airway and ventilation management is the impedance threshold device (ITD). The ITD is a valve that is connected to an airway device (mask, supraglottic airway, endotracheal tube) and reduces air entry to the lungs during the decompression phase of chest compressions.…”
Section: Airway Management Techniquesmentioning
confidence: 99%